2015
DOI: 10.1007/s00340-015-6075-3
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of soot inception in turbulent pressurized flames by simultaneous measurement of laser-induced fluorescence of polycyclic aromatic hydrocarbons and laser-induced incandescence, and correlation to OH distributions

Abstract: Visualization of soot inception in turbulent pressurized flames by simultaneous measurement of laserinduced fluorescence of polycyclic aromatic hydrocarbons and laser-induced incandescence, and correlation to OH distributions, Appl. Phys. B 119 (2015) 717-730.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…For the same flame, various laser-based measurements with low repetition rates are presented in Refs. [3,5,6].…”
Section: Combustor and Operating Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the same flame, various laser-based measurements with low repetition rates are presented in Refs. [3,5,6].…”
Section: Combustor and Operating Conditionmentioning
confidence: 99%
“…Measurements at other operating conditions indicate that the structure of flow field is representative also of flames with other values of pressure, P and φ, whereas the location and rates of soot formation then change significantly [3,5,6]. The study of transient dynamics of soot in the remainder of this work, however, is limited to the single operating condition specified above.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous measurements revealed that the distribution of soot and OH changes with the addition of dilution air. Soot no longer propagates downstream in the central recirculation zone (CRZ) where the OH is dispersed due to the dilution air (Geigle et al 2015b). Recently, their work has focused on soot-turbulence interactions, revealing that soot forms in rich pockets when residence times are favorable, while soot is oxidized by the OH present in the lean zones (Stöhr et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The example of flame extinction will be discussed in greater detail later when we compare Large-Eddy Simulations used for finite-rate kinetic effects against local flame extinction inferred from fast OH-PLIF, which has allowed very thorough validation of the sub-grid turbulent combustion model. Recent developments in PLIF include the imaging of NO [61], soot precursors like Poly-cyclic Aromatic Hydrocarbons (PAH) [62], H atom [63] and HCO [64]. The technical difficulties, resolution issues, lasers and cameras needed are discussed in the original papers.…”
Section: Experimental Diagnosticsmentioning
confidence: 99%